CLO trading and collateral manager bank affiliation - Peristiani, Stavros; Santos, João A.C. (Journal of Financial Intermediation, 2019)
This paper investigates whether the institutional affiliation of a collateralized loan obligation (CLO) manager influences the manager's access to information and risk appetite. We find that CLO managers affiliated with banks start to sell off their positions in loans arranged by their bank well before the onset of default. In contrast, CLO managers affiliated with nonbanks do not lower their exposures to distressed loans. These findings are consistent with bank-affiliated CLO managers being more risk averse, but they could also derive from them having access to valuable information. On close inspection, we find that although bank-affiliated CLO managers are averse to holding any distressed loans, they are also more aggressive at divesting distressed loans arranged by their parent bank, suggesting that they benefit from an information wedge. Besides helping us understand CLO managers’ trading activities, our findings highlight a potential limit to banks’ ability to originate loans and distribute them via their affiliated CLOs.